2021
DOI: 10.1182/blood.2020009346
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal single-cell analysis of cutaneous T-cell lymphoma reveals distinct subclonal tissue-dependent signatures

Abstract: Cutaneous T cell lymphoma (CTCL) is a heterogeneous group of mature T cell neoplasms characterized by the accumulation of clonal malignant CD4+ T cells in the skin. The most common variant of CTCL, Mycosis Fungoides, is confined to the skin in early stages but can be accompanied by extracutaneous dissemination of malignant T cells to the blood and lymph nodes in advanced stages of disease. Sézary Syndrome, a leukemic form of disease is characterized by significant blood involvement. Little is known about the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 51 publications
2
48
0
Order By: Relevance
“…In skin samples, several upregulated pathways were unmasked: T-cell activation, TCR ligation, mitogen-induced transcripts, and cell cycle. Vice versa, T-cell quiescence and markers for resting T-cells were upregulated in blood counterparts [53]. Strikingly, some of those genes were also outlined by Rindler et al in blood of an advanced stage MF patient [54].…”
Section: Single Cell Rna Sequencing Reveals Transcriptional Heterogen...mentioning
confidence: 66%
See 2 more Smart Citations
“…In skin samples, several upregulated pathways were unmasked: T-cell activation, TCR ligation, mitogen-induced transcripts, and cell cycle. Vice versa, T-cell quiescence and markers for resting T-cells were upregulated in blood counterparts [53]. Strikingly, some of those genes were also outlined by Rindler et al in blood of an advanced stage MF patient [54].…”
Section: Single Cell Rna Sequencing Reveals Transcriptional Heterogen...mentioning
confidence: 66%
“…Hence, bulk sequencing will determine average values of fluctuating percentages of malignant and benign cells and cannot assess unique transcriptome expression of tumour cells and its microenvironment [42,46]. Five studies utilized scRNA-seq for CTCL: Three investigated SS [51,52] with one study including a single MF subject [53] and two examined exclusively MF [12,54]. Gaydosik et al [12] sequenced single cells of five advanced stage (IIB-IVA) MF patients.…”
Section: Single Cell Rna Sequencing Reveals Transcriptional Heterogen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to MF's indolent course and the frequency of relapses in MF and SS, treatments focused on the host immune system's role are warranted. A recent finding showed that genetic aberrations and microenvironment cells may promote a transcriptional response fostering rapid malignant expansion, potentially influencing the response to scheduled treatments [193]. Knowledge of the role of the microenvironment and its interaction with neoplastic cells is an unmet need in the light of developing new treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell sequencing of TCR now enables phenotyping of individual T cell clones (31,32) and permits tracking of antigen-specific T cells across tissue compartments and following therapeutic interventions such as immune checkpoint blockade or vaccination (33)(34)(35). Further, TCR is used to phenotype malignant T cells, for example in angioimmunoblastic (36) or cutaneous T cell lymphoma (37,38).…”
Section: Physiologic Natural Barcodesmentioning
confidence: 99%